The history of caravan-sarays emergence on the Great SilkRoad - Salimov , Salimov A.M. (Рroblems of engineering and professional education, 2022)
The article considers the history of caravan-sarays on the Great Silk Road, which is one of the signs of high development of art of the period. In this sense, the typology of caravan-sarays is crucial, caravan-sarays can be in Muslim countries of Near and Middle East and Northern Africa along the prior trade caravan ways.